Halting Schistosoma haematobium - Associated Bladder Cancer - Botelho, Monica C. (2017)
Background: At present schistosomiasis is endemic in 78 countries, affecting more than 260 million people. Schistosomiasis haematobia alone affects more than 112 millions. Evidence Acquisition: We performed a computerized search of in PubMed database with keywords: Bladder Cancer Cost and Schistosomiasis Mass Treatment. Results: Bladder cancer is an important sequelae of this infection. In low-resource countries, where this disease is endemic, individuals inflicted with bladder cancer have very limited access to treatment and death is most probably certain. Conclusions: Mass treatment with praziquantel is an easy, safe, and inexpensive treatment that could save the lives of thousands and reduce the morbidity of millions.